Alzheimer's disease: Targeting the Cholinergic System - H. Ferreira-Vieira, Talita; M. Guimaraes, Isabella; R. Silva, Flavia; M. Ribeiro, Fabiola (Current Neuropharmacology, 2016)
Acetylcholine (ACh) has a crucial role in the peripheral and central nervous systems. The enzyme choline acetyltransferase (ChAT) is responsible for synthesizing ACh from acetyl-CoA and choline in the cytoplasm and the vesicular acetylcholine transporter (VAChT) uptakes the neurotransmitter into synaptic vesicles. Following depolarization, ACh undergoes exocytosis reaching the synaptic cleft, where it can bind its receptors, including muscarinic and nicotinic receptors. ACh present at the synaptic cleft is promptly hydrolyzed by the enzyme acetylcholinesterase (AChE), forming acetate and choline, which is recycled into the presynaptic nerve terminal by the high-affinity choline transporter (CHT1). Cholinergic neurons located in the basal forebrain, including the neurons that form the nucleus basalis of Meynert, are severely lost in Alzheimer’s disease (AD). AD is the most ordinary cause of dementia affecting 25 million people worldwide. The hallmarks of the disease are the accumulation of neurofibrillary tangles and amyloid plaques. However, there is no real correlation between levels of cortical plaques and AD-related cognitive impairment. Nevertheless, synaptic loss is the principal correlate of disease progression and loss of cholinergic neurons contributes to memory and attention deficits. Thus, drugs that act on the cholinergic system represent a promising option to treat AD patients.
Keywords: Alzheimer’s disease